Industrial Japan and industrious Japanese - Takahata, Seiichi (Nissho Co., 1968)
This book explains in fascinating detail how economic and social transformations in pre-1600 Japan led to an industrious revolution in the early modern period and how the fruits of the Industrious Revolution are what have supported Japan since the eighteenth century, improving living standards and leading to the formation of the work ethic of modern Japan.